Przestrzenne aspekty zrównoważonego rozwoju we współpracy międzyregionalnej Dolnego Śląska i Saksonii - Adamczuk, Franciszek (Spatial aspects of sustainable development in interregional co-operation between Lower Silesia and Saxony, 2007)
The article discusses spatial aspects of sustainable development in interregional co-operation between lower Silesia and Saxony. The author refers to all important documents concerning spatial development in both regions. The paper focuses on the Regional Development Concept for Saxony (2003) and the Development Strategy of Dolnośląskie Voivodship 2020. The last part of the paper includes conclusions and evaluation of the problem.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 258-272